2014
DOI: 10.1002/2014wr015521
|View full text |Cite
|
Sign up to set email alerts
|

Cholera in the Lake Kivu region (DRC): Integrating remote sensing and spatially explicit epidemiological modeling

Abstract: Mathematical models of cholera dynamics can not only help in identifying environmental drivers and processes that influence disease transmission, but may also represent valuable tools for the prediction of the epidemiological patterns in time and space as well as for the allocation of health care resources. Cholera outbreaks have been reported in the Democratic Republic of the Congo since the 1970s. They have been ravaging the shore of Lake Kivu in the east of the country repeatedly during the last decades. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…[56]). We also note that in endemic settings, provided that space-time data are available, other mathematical tools could be more appropriate than those used in this work, including time-series analysis [19,21,57,58], spatially implicit [20] and Markov chain models [22,59].…”
Section: Discussionmentioning
confidence: 99%
“…[56]). We also note that in endemic settings, provided that space-time data are available, other mathematical tools could be more appropriate than those used in this work, including time-series analysis [19,21,57,58], spatially implicit [20] and Markov chain models [22,59].…”
Section: Discussionmentioning
confidence: 99%
“…A large palette of modeling techniques have been applied to study cholera (for an overview see [32]). Here we choose the MDIMC framework proposed by Reiner et al [13] in which the observed monthly cholera attack rates are categorized into discrete states of cholera intensity, and the space-time dynamics of transmission modeled by a inhomogeneous Markov Chain [13, 32].…”
Section: Methodsmentioning
confidence: 99%
“…Here we choose the MDIMC framework proposed by Reiner et al [13] in which the observed monthly cholera attack rates are categorized into discrete states of cholera intensity, and the space-time dynamics of transmission modeled by a inhomogeneous Markov Chain [13, 32]. The transition from cholera in state i at time t to state j at time t + 1 ( X k,t = i ) → ( X k,t +1 = j ) occurs with baseline probability p i,j .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further our understanding of plankton dynamics in Lake Kivu (Figure 1), we assess and attempt to optimize a remotely-sensed proxy for plankton biomass. This could possibly have implications for the mathematical modeling of cholera dynamics around Lake Kivu, described in Finger et al (2014).…”
Section: Contextmentioning
confidence: 99%